EXPLORING THE CYC CIS-TEM: A LITERATURE REVIEW OF QUEER AND TRANS TOPICS IN CHILD AND YOUTH CARE - Walker, Mattie (International Journal of Child, Youth and Family Studies, 2021)
Although Child and Youth Care (CYC) sees itself as a field that embraces diversity and complexity, there is a notable lack of discussion of sexual and gender diversity: queer and trans topics are rarely taken up across CYC research, practice, and pedagogy. Through a systematic literature review of articles published between 2010 and early 2020 in six journals with a focus on CYC practice, research, and theory, this article assesses how queer, trans, Two-Spirit, and nonbinary identities and topics are being discussed in the current CYC literature and reveals a conspicuous absence of publication on these topics. In a 10-year period, across six CYC publications comprising over 4000 published articles, only 36 articles focused on queer and LGBT issues (by covering both sexual and gender diversity) and, of those, only eight articles specifically focused on gender diversity or trans topics. No articles were found within any of the reviewed publications that specifically focused on Two-Spirit identities or topics and only one article mentioned nonbinary identities. Through exploring how and where queer and trans, Two-Spirit, and nonbinary identities and topics are being discussed, this review asks how we as a CYC field might begin to make space for these topics within our field and practice, in order to work towards social change that shifts our field and challenges the cis-heteronormative CYC system.